Quantitative trait loci associated with root elongation ability of rice under nitrogen-deficient condition - Manangkil, Jennifer M.; Suralta, Roel R.; Castillo, Mark Philip B.; Estrada, Sherilyn B.; Banting, Maybell DM; Mallari, Rachelle P.; Obara, Mitsuhiro; Mananghaya, Teodora E.; Niones, Jonathan M.; Undan, Jerwin R. (2019)
Nitrogen (N) is an important nutrient influencing the growth and yield in rice. Root plasticity is a key trait in the higher uptake of nutrient from the soil, especially in conditions where some major nutrients such as N is under optimal. In this study, a total of 168 BC1F4 mapping population from a cross between Malay 2 and US-2 and their parents were grown in hydroponics with deficient (5 µM) and sufficient (500 µM) N for 8 days to identify putative quantitative trait loci (QTLs) associated with root elongation. Eighty-three (83) markers were used in QTL detection using composite interval mapping. Results showed that US-2 had significantly greater shoot length and number of nodal roots than Malay 2 under N-deficient conditions. Around 19.6 and 26.8% of the population in N-deficient and N-sufficient conditions, respectively, had either longer or similar seminal root length compared with US-2. For the allele distribution, 43.1% of the population had homozygous allele for Malay 2, 20.9% had homozygous allele for US-2, and 8.4% had heterozygous allele for both parents. A total of eight putative QTLs associated with seminal root length (qSRL11.1 and qSRL2.1); number of nodal roots (qNNR6.1, qNNR11.1, and qNNR11.2); root dry weight (qRDW11.1 and qRDW11.2); and shoot length (qSL2.1) in chromosome 2, 6, and 11 regions were detected under both N treatments. (Author's abstract)